2013
DOI: 10.1103/physrevd.87.043523
|View full text |Cite
|
Sign up to set email alerts
|

Isotropy theorem for cosmological Yang-Mills theories

Abstract: We consider homogeneous non-abelian vector fields with general potential terms in an expanding universe. We find a mechanical analogy with a system of N interacting particles (with N the dimension of the gauge group) moving in three dimensions under the action of a central potential. In the case of bounded and rapid evolution compared to the rate of expansion, we show by making use of a generalization of the virial theorem that for arbitrary potential and polarization pattern, the average energy-momentum tenso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 42 publications
2
32
0
Order By: Relevance
“…Although the work on ultralight fields has been mainly concerned with scalar fields, there are recent results on higher spin fields. It has been shown that abelian vectors at the background [22] and perturbation level [23], non-abelian vectors [24] and arbitrary-spin fields [25] behave in a similar way. Interestingly, the results of [25] show that it is possible to achieve an isotropic model of higher-spin dark matter as long as it is rapidly oscillating.…”
Section: Jhep08(2018)073mentioning
confidence: 95%
“…Although the work on ultralight fields has been mainly concerned with scalar fields, there are recent results on higher spin fields. It has been shown that abelian vectors at the background [22] and perturbation level [23], non-abelian vectors [24] and arbitrary-spin fields [25] behave in a similar way. Interestingly, the results of [25] show that it is possible to achieve an isotropic model of higher-spin dark matter as long as it is rapidly oscillating.…”
Section: Jhep08(2018)073mentioning
confidence: 95%
“…His results can be recovered by means of a generalization of the virial theorem [60]. Recently, it has been shown that a fast oscillating abelian vector [61], non-abelian vector [62,63] or arbitrary spin field [64] will behave in a very similar way.…”
Section: Introductionmentioning
confidence: 90%
“…The main problem which arises in the case of vectors or higher spin fields is that coherent homogeneous fields typically break isotropy. However it has been recently shown (see [54,55] for abelian vector fields, [56] for nonabelian theories and [57] for arbitrary spin) that for rapidly oscillating coherent fields, even though the field evolution is generically anisotropic, the average energy-momentum tensor is not. In particular, for massive fields it is straightforward to show that the average energy density scales as a −3 .…”
Section: Jhep02(2017)064mentioning
confidence: 99%